Multiple-breath washout outcomes are sensitive to inflammation and infection in children with cystic fibrosis - Ramsey, K.; Foong, R.; Grdosic, J.; Harper, A.; Skoric, B.; Clem, C.; Davis, M.; Turkovic, L.; Stick, S.; Davis, S.; Ranganathan, S.; Hall, Graham (2017)
© 2017 by the American Thoracic Society. Rationale: The lung clearance index is a measure of ventilation distribution derived from the multiple-breath washout technique. The lung clearance index is increased in the presence of lower respiratory tract inflammation and infection in infants with cystic fibrosis; however, the associations during the preschool years are unknown. Objectives: We assessed the ability of the lung clearance index to detect the presence and extent of lower respiratory tract inflammation and infection in preschool children with cystic fibrosis. Methods: Ventilation distribution outcomes were assessed at 82 visits with 58 children with cystic fibrosis and at 38 visits with 31 healthy children aged 3-6 years. Children with cystic fibrosis also underwent bronchoalveolar lavage fluid collection for detection of lower respiratory tract inflammation and infection. Associations between multiple-breath washout indices and the presence and extent of airway inflammation and infection were assessed using linear mixed effects models. Results: Lung clearance index was elevated in children with cystic fibrosis (mean [SD], 8.00 [1.45] ) compared with healthy control subjects (6.67 [0.56]). In cystic fibrosis, the lung clearance index was elevated in individuals with lower respiratory tract infections (difference compared with uninfected [95% confidence interval] , 0.62 [0.06, 1.18]) and correlated with the extent of airway inflammation. Conclusions: These data suggest that the lung clearance index may be a useful surveillance tool for monitoring the presence and extent of lower airway inflammation and infection in preschool children with cystic fibrosis.